Interaction of remdesivir with clinically relevant hepatic drug uptake transporters - Nies, Anne T.; König, Jörg; Hofmann, Ute; Kölz, Charlotte; Fromm, Martin; Schwab, Matthias (Pharmaceutics, 2021)
Remdesivir has been approved for treatment of COVID-19 and shortens the time to recovery in hospitalized patients. Drug transporters removing remdesivir from the circulation may reduce efficacy of treatment by lowering its plasma levels. Information on the interaction of remdesivir with drug transporters is limited. We therefore assessed remdesivir as substrate and inhibitor of the clinically relevant hepatic drug uptake transporters organic anion transporting poly-peptide (OATP)-1B1 (SLCO1B1), its common genetic variants OATP1B1*1b, OATP1B1*5, OATP1B1*15, as well as OATP1B3 (SLCO1B3), OATP2B1 (SLCO2B1) and organic cation transporter (OCT)-1 (SLC22A1). Previously established transporter-overexpressing cells were used to measure (i) cellular remdesivir uptake and (ii) cellular uptake of transporter probe substrates in the presence of remdesivir. There was a high remdesivir uptake into vector-transfected control cells. Moderate, but statistically significant higher uptake was detected only for OATP1B1-, OATP1B1*1b and OATP1B1*15-expressing cells when compared with control cells at 5 µM. Remdesivir inhibited all investigated transporters at 10 µM and above. In conclusion, the low uptake rates suggest that OATP1B1 and its genetic variants, OATP1B3, OATP2B1 and OCT1 are not relevant for hepatocellular uptake of remdesivir in humans. Due to the rapid clearance of remdesivir, no clinically relevant transporter-mediated drug-drug interactions are expected.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Drug transporters; Drug-drug interaction; Inhibition; OATP1B1; OATP1B3; OATP2B1; OCT1; Remdesivir